Analysis of insecticides in long-lasting insecticidal nets using X-ray fluorescence spectroscopy and correlation with bioefficacy - Koinari, Melanie; Bubun, Nakei; Wilson, David; Anetul, Evodia; Timinao, Lincoln; Johnson, Petrina; Daly, Norelle L.; Laman, Moses; Freeman, Tim; Karl, Stephan (Frontiers in Parasitology, 2023)
Background: Long lasting insecticidal nets (LLINs) are a key vector control tool used for the prevention of malaria. Active ingredient (AI) measurements in LLINs are essential for evaluating their quality and efficacy. The main aim of the present study was to determine the utility of X-ray fluorescence (XRF) spectroscopy as a suitable field deployable tool for total AI quantification in LLINs.Methods: New and unused LLIN samples containing deltamethrin (PermaNet® 2.0, n = 35) and alpha-cypermethrin (SafeNet®, n = 43) were obtained from batches delivered to Papua New Guinea (PNG) for mass distribution. Insecticides were extracted from the LLINs using a simple extraction technique and quantified using liquid chromatography mass spectrometry (LC-MS). The LC-MS results were correlated with XRF spectroscopy measurements on the same nets. Operators were blinded towards the identity of the nets. Bioefficacy of the LLIN samples was tested using WHO cone bioassays and test results were correlated with total AI content.The results indicate correlation between quantitative XRF and LC-MS. Interestingly, the total AI content was negatively correlated with bioefficacy in PermaNet® 2.0 (especially, in recently manufactured nets). In contrast, AI content was positively correlated with bioefficacy in SafeNet®. These results indicate that the chemical content analysis in predelivery inspections does not always predict bioefficacy.XRF is a promising field deployable tool for quantification of both deltamethrin and alpha-cypermethrin coated LLINs. Since total AI content is not always a predictor of the efficacy of LLINs to kill mosquitoes, bioefficacy measurements should be included in predelivery inspections.